2005
DOI: 10.1681/asn.2004070597
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anemia and Left Ventricular Hypertrophy on Cardiovascular Disease in Patients with Chronic Kidney Disease

Abstract: Left ventricular hypertrophy (LVH) and anemia are highly prevalent in moderate chronic kidney disease (CKD). Because anemia may potentiate the adverse effects of LVH on cardiovascular outcomes, the effect of both anemia and LVH on outcomes in CKD was examined. Data from four community-based longitudinal studies were pooled: Atherosclerosis Risk in Communities Study, Cardiovascular Health Study, Framingham Heart Study, and Framingham Offspring Study. Serum creatinine levels were calibrated indirectly across stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
121
2
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 190 publications
(133 citation statements)
references
References 26 publications
1
121
2
6
Order By: Relevance
“…Hypoxiainduced altered renal sympathetic nerve activity may differentially regulate glomerular haemodynamics [28]. Close associations between anaemia and cardiac disorders, including left ventricular (LV) hypertrophy and heart failure [29,30], may also provide a basis for explaining the anaemia-induced loss of kidney function in diabetes, as these conditions are associated with decreased effective renal blood flow. Indeed, an increase in LV mass has been reported to occur early in the course of diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxiainduced altered renal sympathetic nerve activity may differentially regulate glomerular haemodynamics [28]. Close associations between anaemia and cardiac disorders, including left ventricular (LV) hypertrophy and heart failure [29,30], may also provide a basis for explaining the anaemia-induced loss of kidney function in diabetes, as these conditions are associated with decreased effective renal blood flow. Indeed, an increase in LV mass has been reported to occur early in the course of diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few of the historical prospective and retrospective studies in dialysis patients have analyzed, with adjustments for comorbidities, the association between hemoglobin level and outcome (43)(44)(45)(46). These studies have generally shown a strong and consistent association between higher hemoglobin or hematocrit levels and better outcome (43)(44)(45)(46)(47)(48)(49).…”
Section: Anemia and Hdmentioning
confidence: 95%
“…Left ventricular hypertrophy (LVH) was defined on the basis of electrocardiogram criteria. 24 BMI was calculated as (weight in kg/height in m 2 ). Diuretic use included thiazide, loop, and potassium-sparing diuretics, because the limited access data did not universally differentiate diuretic class.…”
Section: Other Variablesmentioning
confidence: 99%